A new species of Trigonella sect. Ellipticae (Leguminosae-Papilionoideae) from Iran, including cytogenetic and anatomical notes - Ranjbar, Massoud; Hajmoradi, Zahra (Phytotaxa, 2015)
A new species, Trigonella bakhtiarica, from the Iranian province Chahar Mahal Va Bakhtiari is described, illustrated and compared to its most closely related species, T. aphanoneura. Trigonella bakhtiarica has a longer corolla and differs in the shape, surface and size of its pods, which are taxonomically informative characters in Trigonella sect. Ellipticae. Chromosome counts and meiosis assays show that both species are diploid, and that their euploid plants possess a somatic chromosome number of 2n = 2x = 16, which is consistent with the predicted base number of x = 8.